OPTIMALISASI PEKARANGAN DENGAN TEKNOLOGI BIOFLOK DAN HIDROPONIK DI DESA JENETAESA - Gunadi, Hendrik; Depthios, Erick; Djunaidy, Machmud; Tumimba, Yelvira Monica; Mangetan, Larissa; Batti, Elsa; Welni, Welni; Duruk, Meichelle (Jurnal Abdimas Musi Charitas, 2024)
The challenge of utilizing infertile and limited yard space has been a persistent issue for the people of Jenetaesa Village. In response, the Sipakatau Farmers Group Association, in collaboration with Universitas Kristen Indonesia Paulus, introduced an innovative approach through Biofloc and Hydroponic technology. This initiative, part of a Community Service Program, aims to empower farmers with knowledge and skills to optimize land productivity. The method integrates fish farming using a Biofloc system with vegetable cultivation through hydroponic-verticulture. This synergy efficiently utilizes land, feed, and nutrients by recycling organic materials into fish feed while providing essential nutrients for vegetables. The Biofloc system enhances water quality, and the nutrient-enriched water supports hydroponic plant growth without the need for synthetic fertilizers. The program has successfully increased household income by providing sustainable fish and vegetable yields, while also meeting the nutritional needs of farming families. This innovative approach exemplifies sustainable agriculture in rural areas.